Targeting PFKFB4 Biomimetic Codelivery System Synergistically Enhances Ferroptosis to Suppress Small Cell Lung Cancer and Augments the Efficacy of Anti‐PD‐L1 Immunotherapy - Xiang Liu; Jingjun He; Haoxuan Ying; Cuiying Chen; Chongyang Zheng; Peng Luo; Weiliang Zhu; Ting Wei; Bufu Tang; Jian Zhang (Advanced Science)
Abstract Small cell lung cancer (SCLC) is an extremely aggressive and highly malignant type of lung cancer that frequently develops resistance and recurrence following initial treatment. Paclitaxel (PTX) is a second‐line therapeutic option for SCLC patients with resistance to first‐line treatment. However, its clinical application is limited due to suboptimal efficacy and the risk of hypersensitivity reactions. To address these challenges, a novel therapeutic strategy employing a cationic liposome‐based biomimetic drug co‐delivery system, siPFKFB4/PRLPTX@RBCM‐cRGD, which simultaneously delivers paclitaxel and PFKFB4‐targeting small interfering RNA (siRNA) to SCLC cells and tissues is proposed. These findings demonstrate that this co‐delivery system can induce ferroptosis in SCLC cells, thereby enhancing their sensitivity to paclitaxel. Moreover, It promotes the infiltration of immune cells and the secretion of cytokines within the SCLC immune microenvironment, effectively activating anti‐tumor immunity. When combined with anti‐PD‐L1 antibodies, it further potentiates anti‐tumor immune responses. These results suggest that the biomimetic codelivery system not only induces ferroptosis to enhance paclitaxel efficacy but also reprograms the SCLC immune microenvironment, thereby potentiating the effects of anti‐PD‐L1 immunotherapy and providing a promising new therapeutic strategy for SCLC.